Interactions between active tectonics and gravitational deformation along the Billecocha fault system (Northern Ecuador): Insights from morphological and paleoseismological investigations. (November 2021) - Jomard, H.; Saqui, D.; Baize, S.; Alvarado, A.; Bernard, B.; Audin, L.; Hidalgo, S.; Pacheco, D.; Ruiz, M.; Segovia, M.
Abstract: The Billecocha plateau (4000 m a.s.l.) lies in the high elevation Ecuadorian Andes volcanic arc. It overhangs by 2000 m above the interandean valley. Both the plateau and surrounding volcanoes are heavily affected by active faulting characterized by straight, sharp and discontinuous scarps within a 6 km wide and 24 km long corridor. Contrasting interpretations have been proposed to explain the expression at surface of the so-called Billecocha fault system (BFS), from normal faulting related to postglacial elastic rebound or gravitational processes, to right-lateral faulting compatible with the North-Andean Sliver tectonic regime. The instrumental seismicity recorded around the BFS is low, however, a M~7 earthquake heavily struck the region in 1868. With the aim to discuss the kinematic and coseismic nature of the encountered deformations as well as the seismogenic character of the BFS, we performed (1) morphological analysis to map and quantify evidence of active faulting and (2) paleoseismological investigations across the longer segment of the fault system. In three trenches, we show that surface deformations are at least partly coseismic in origin during the Holocene with a minor lateral component, the last paleoseismic event being compatible in date with the 1868 earthquake. In addition, some of the enlightened paleoseismic events could have occurred in relationship with volcanic eruptions of the surrounding volcanoes. While field evidence of reverse and strike slip faulting suggests that regional tectonics could be involved, the geomorphological signature of the BFS at the mountain scale, as seen on the digital surface model, can partly be related to the development of deep seated gravitational deformations, hence suggesting an interaction between boundary (i.e. tectonic, volcanic) and body forces (i.e. gravity, post-glacial rebound). Further studies are however mandatory to better address the influence of each process at the BFS, in particular geodetic and seismological surveys. Given the available data, we suggest that the BFS could actually correspond to the distributed surface expression of the tectonic reactivation of the inherited Pujilí suture, enhanced by gravitational phenomenon. In this light, paleoearthquakes identified along the BFS may help evidencing the recurrence of major events in the region. However, it also imply that surface deformations along the BFS shall not be used without a careful and more detailed field work to derive fault slip rates for seismic hazard calculations. Highlights: The Billecocha fault system (BFS) shows spectacular morphologies in a 6 × 24km area. Paleoseismological analysis revealed up to 7 coseismic ruptures in the last 6ky. Coseismic ruptures may not be related to primary surface faulting. The surface expression of active faulting is enhanced by gravitational deformations. The 1868 Ibarra earthquake was probably registered along the Billecocha faults.